Preparation of wastelage using poultry droppings with maize stover and its nutrient content as ruminant feed (Bangladesh Journal of Animal Science, 2020)
An experiment was undertaken with caged layer excreta (CLE) treated maize stover and ensiled to investigate its potentiality as ruminant feed. Chopped maize stovers were preserved in plastic containers under airtight condition at room temperature based on the treatments as T0 (0% CLE), T1 (20% CLE), T2 (40% CLE) and T3 (60% CLE) to investigate physical quality, chemical composition, in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) content at 0, 30, 60 and 90 days. The CP and Ash were increased (P